2019
DOI: 10.1590/1807-1929/agriambi.v23n12p966-971
|View full text |Cite
|
Sign up to set email alerts
|

Maize productivity in succession to cover crops, nitrogen fertilization and inoculation with Azospirillum brasilense

Abstract: The use of microorganisms in agriculture such as Azospirillum brasilense and the cultivation of cover crops in the off season, together with nitrogen fertilization, may be interesting alternatives to increase crop yield. The objective of this study was to evaluate the growth, production and nitrogen concentration of maize grown in succession to cover crops and their interactions with A. brasilense inoculation and topdressing mineral N fertilization. The experiment was conducted on Oxisol, in randomized block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In this research, it was proved that cover crops positively affect the growth and yield parameters of popcorn maize. It was shown that field pea (CC2) mainly supported chlorophyll synthesis and biomass accumulation in seasons with relatively optimal meteorological conditions, resulting thus in higher grain yield, while in unfavorable seasons, such as 2021, it contributed to greater grain yield achievement, indicating the importance of leguminous CC, i.e., catch CC, for maize productivity ( Santos et al., 2019 ). Marcillo and Miguez (2017) specified that maize yield could be increased up to 33%, after leguminous CC, when zero tillage was used or N fertilization was low.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, it was proved that cover crops positively affect the growth and yield parameters of popcorn maize. It was shown that field pea (CC2) mainly supported chlorophyll synthesis and biomass accumulation in seasons with relatively optimal meteorological conditions, resulting thus in higher grain yield, while in unfavorable seasons, such as 2021, it contributed to greater grain yield achievement, indicating the importance of leguminous CC, i.e., catch CC, for maize productivity ( Santos et al., 2019 ). Marcillo and Miguez (2017) specified that maize yield could be increased up to 33%, after leguminous CC, when zero tillage was used or N fertilization was low.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical determinations made in this study contribute to a better understanding of how auxin induction, culture media, and PGPR inoculation affect the physiology of woody plants. Research lines currently being carried out aim to study the diversity of new isolates of A. brasilense and select bacteria according to their ability to promote plant growth, from native forage, 46,47 cereals, 16,19,44,[48][49][50][51][52][53] fruit trees, 54 microplants, 55 as well as the ability to promote the growth of microalgae. [56][57][58] Other lines of work study the mechanisms and molecules involved in the establishment of plant-microorganism interaction.…”
Section: The Bacterium: Azospirillummentioning
confidence: 99%
“…The effect of legume cover crops in maize yield was related in a meta-analysis by , in which the yield was 21% higher under cover crop compared to fallow. Santos Júnior et al (2019) showed in an experiment with maize-legumes cover crop rotation that the grain yield improvement provided by legumes cover crop depends on the specie adopted in the succession and can be higher or neutral compared to the treatment without cover crop.…”
Section: Effects Of Cover Crop Rotation Systems In Maize Yield Responsementioning
confidence: 99%